Research of the Shifting Characteristic of Planetary Transmission with using Tooth Brake - Li Yaxi; Ma Biao; Li Heyan; Zhu Li’an (Jixie chuandong)
The dynamics model of a two-speed planetary transmission is established by using the virtual displacement principle,the dynamic shifting processes comparison and simulation analysis between the planetary transmission using tooth brake and friction brake are carried out. The different joint speed effects on the transmission characteristics are also analyzed through the simulation. The simulation results show that the maximum torque impact of the planetary transmission using tooth brake is lower than using friction brake in the same shifting time. The larger the joint speed difference of the planetary transmission using tooth brake is and the smaller the shifting time is,the greater the maximum torque impact is still lower than the planetary transmission using friction brake.